Pagelaran Budaya Jepang Cosplayer dalam Perspektif Dramaturgi - Haes, Putri Ekaresty; Pratiwi, Nuning Indah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The phenomenon of anime television shows and comic books originating from Japan provides space for the development of Japanese popular culture in Bali. The art of dress in Japanese popular cultures such as Harajuku Style (such as Lolita, Visual Kei, Ganguro and the costume player) has shifted traditional Japanese clothing such as kimono and Yukata. A cospalyer admires a certain anime, manga or costume player character and tries to present the character in several Japanese cultural performances held in the city of Denpasar and Badung Sub-district. The purpose of this research is to study the front stage (backstage) of the costume players. This research is qualitative, using data collection techniques such as observation, interviews and documentation techniques. The result from this research explained that on dramaturgy perspective the existence of stage in human life between the front stage and the backstage of a costume player is two different sides, even contradictory, but some of them had the same character. The Presentation of the Japanese’s fashion styles are very disserving (adapted from the characters) and full of creativities, so all the costume player will be the center of attention in Japanese cultural performances conducted in The Japan Pagelaran of Udayana (D’JaFU), CLAS: H Bali Sakura Matsuri, dan Fella Market Cosplay Competition.